Analysis of the Need for the Use of the First 1000 Days of Life (HPK) Education E- Module to Educate Mothers About Stunting - Erma Agustina; Tri Murwaningsih; Eka Budhi Santosa (Social, Humanities, and Educational Studies (SHES): Conference Series, 2023)
Stunting has an impact on children starting from the beginning of a child's life and will continue in the human life cycle. Stunting has a negative impact on children's brain development. Early in life causes a slowdown and reduc-tion in the number and development of brain cells and other organs. There is a need for learning media to increase pregnant women's knowledge of the dangers of stunting. The aims of this study were to obtain: 1) an overview of the use of e-module media as a means of learning the dangers of stunting for pregnant women, 2) views and constraints faced by mothers in raising awareness of the dangers of stunting, 3) learning media formulations that need attention that can developed to increase awareness of the dangers of stunting. The results of the observations were in the form of an instrument for assessing the needs of elementary school students which were analyzed descriptively qualitatively. The researcher found that the use of social media as a learning resource in the process of understanding the dangers of stunting has been carried out in the field, but has not been implemented optimally, namely: 1) there are obstacles to unstructured and complete information, be-cause detailed and focused presentation of material is required 2) the materi-al is not pack aged interestingly mak es mothers who use it less enthusiastic, and 3) learning media that need to be developed to increase awareness of the dangers of stunting are e-modules to increase awareness of the dangers of stunting.